Beyond numbers: accounting ethics and accountability in the digital age - Mohd Zain, Azizah; Nazruddin, Noor Suriani; Naiimi, Nazirah (Faculty of Accountancy, 2025)
Accounting is one of the most trusted and respected professions in the world. This is because it is closely linked to honesty, trust, and responsibility. The word "accountant" comes from "accountable", which means being responsible and ready to explain their actions. An accountant is not just only a person who manages money or prepares financial reports, they also play a vital role in ensuring that businesses act responsibly and ethically in their financial practices (Duska, Duska, & Ragatz, 2011 ).